Sistem Informasi Pembelian dan Penjualan Outdoor Tools Berbasis Desktop - Yuniatin Trisnawati Dwi Kusuma Wardani; Ismi Rohani (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2022)
System development is carried out to produce a system that can help process transactions related to purchases and sales. System development is designed to make a computerized sales and purchasing system so it will facilitate all activities quickly, easily and accurately. System development carried out in Alambara Adventure because it still uses a manual system in running the sales and purchasing system, so that the manual implementation process is still experiencing time and accuracy problems. The method used in this research is the descriptive analysis method. Information systems applied in the sale and purchase of outdoor equipment are in the form of internet and desktop-based information systems. The system is built using Borland Delphi 7 and Microsoft Access as a database and there is automation for coding, among others, item code, customer, supplier, and invoice number. System analysis starts from analyzing the running system then analyzing system weaknesses and finally making a system requirements analysis. The system design stage starts from making context diagrams, data flow diagrams, and flowcharts, then making input and output designs. The novelty of the system designed at Alambara Adventure is the testing phase carried out on the user through Acceptance testing at the system design stage and at the end of the system design.